Community Empowerment In Terawan Village Through Training On FoodProcessing From Banana Trunk Waste As A Creative Business Idea - Azizah, Salma (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2025)
Terawan is a village located in Seruyan Raya District, Central Kalimantan, Indonesia. Terawan Village is renowned for its abundant natural resources, particularly palm oil plantations and a variety of dried fish, which are marketed locally and for export. Therefore, the local population relies primarily on palm oil company employees and fishermen for their livelihoods. Banana plants are also widely cultivated by the local community. However, only the fruit and leaves are used, resulting in underutilization as the banana stems are often discarded. Banana stems can be utilized with a little innovation to create products with high economic value. It is hoped that this training will equip the community with skills in enhancing the benefits of banana plants, fostering entrepreneurial interest and generating creative business ideas that can be used as alternative livelihoods. The training methods used in this training include lectures, discussions, and live demonstrations on how to process banana stem chips, followed by a question and answer session. This training is aimed at women in the Family Welfare Movement (PKK) in Terawan Village. The activity, held on August 30, 2023, achieved significant results, including improving the skills and understanding of women on how to process banana stem waste into economically valuable banana stem chips. The activity went well and met expectations, thanks to strong cooperation and the high level of enthusiasm shown by the 23 participants.